Pendampingan Pelatihan Pengelolaan Stok Usaha Menggunakan Microsoft Excel untuk Perusahaan Green Naturale - Gemiartha, Celine Morgan; Kurniawan, Abraham Ivan; Yusuf, Keona Adeline; Hadap, Billy Mathew; Malelak, Mariana Ing (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Inefficient stock recording can result in deadstock, therefore it is important for business owners to have systematic inventory record management. So, this community service activity aims to solve Green Naturale's problems related to managing records, making profit and loss reports, and analyzing stock turnover. To answer the needs, students conducted intensive training for 3 weeks to increase the knowledge of MSME owners related to Microsoft Excel and its utilization in answering existing problems. For training assistance, students organized 3 meetings. At the first meeting, students explained basic knowledge related to Microsoft Excel, at the second meeting students conducted training on the use of Microsoft Excel templates, and at the last meeting the owner carried out practices and simulations ending with a question and answer session and evaluation. After the community service activity, the owner's ability to use Microsoft Excel has increased significantly and this has an impact on managing inventory records more efficiently, recording accurate and transparent profit and loss and analyzing better inventory turnover